PENGUATAN LAYANAN APARATUR DALAM MODEL VOUSINAS UNTUK MENCEGAH PENYELEWENGAN PENGELOLAAN DANA DESA - Wibowo, Riyan Surya; Zulfikar, Zulfikar; Achyani, Fatchan Fatchan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to identify variables that influence the occurrence of misappropriation of village funds and determine effective measures to prevent it. This study used a quantitative approach using questionnaires as the survey technique. Primary data was collected from 97 respondents who were village administrators in Banyudono Subdistrict. Statistical analysis was conducted using multiple linear regression. The hypotheses regarding the influence of superior pressure, internal control system, individual morality, apparatus ability, and leadership on preventing village fund fraud were rejected. However, the hypothesis regarding the influence of unethical behavior was accepted, highlighting the significant negative impact of such behavior on fraud prevention. This study provides deep insight into the factors that influence fraud in the management of village funds and demonstrates the need for effective preventive measures. The results of this study can be used as a basis for developing more transparent and accountable village fund management strategies. This research makes a new contribution to the understanding of fraud in the management of village funds by adapting the Fraud Hexagon Hypothesis (Vousinas, 2019) to the context of village fund management, which involves aspects of collusion as an additional factor that can influence the occurrence of fraud.